Effectiveness of Compassion Focused Therapy in the reduction of Self-Criticism and Parental Guilt of Mothers of Children with Phenylketonuria Syndrome: A Quasi-Experimental Study - Borzoo Amirpour; Zahra Asgarpour; Mehrdad AhmadiFar (Mazandaran University of Medical Sciences, 2024)
Introduction and purpose: Children's training is difficult enough for any family. Yet, for the parents of a child with a disability, worrying about their future can be overwhelming. In the meantime, a series of problems, including adverse psychological consequences, are imposed on mothers due to their closeness and more engagement in parenting duties as the cost of caring for these children. The present study aimed to assess the effectiveness of compassion-focused therapy in reducing self-criticism and parental guilt of mothers with children with Phenylketonuria syndrome. Methods: This applied quasi-experimental study was conducted based on a pre-test, post-test, control group design. The statistical population of the study consisted of 37 mothers with children suffering from phenylketonuria in Delfan in 2023. Out of this population, 30 cases were selected and randomly assigned to two intervention and control groups(n=15 in each group). The intervention group (Based on the treatment protocol of Gilbert and Neff, 2007) received compassion-focused therapy training during eight two-hour sessions once a week. In order to collect data before and after the treatment program, two questionnaires, Hosseini Tari's parental guilt (2019) and Saadati Shamir's self-criticism (2018), were used. Data were analyzed in SPSS software (version 27) using descriptive indices and multivariate covariance analysis. Results: The findings pointed out that after controlling the scores of the pre-test stage, there was a significant difference between the intervention and control groups in the post-test scores of self-criticism (Eta=0.232; P=0.017; F=6.636) and parental guilt (Eta=0.629; P=0.001; F=7.366). Conclusion: As evidenced by the results of the present study and in connection with the practical background of the research, compassion-focused therapy significantly reduces self-criticism and parental guilt of mothers with children with phenylketonuria. Therefore, it is suggested to use compassion-focused therapy in psychotherapy and rehabilitation counseling for parents of children with special needs in order to improve the psychological health of their mothers.